Hypopharyngeal Squamous Cell Carcinoma: Three-Dimensional or Intensity-Modulated Radiotherapy? A Single Institution’s Experience - Katsoulakis, Evangelia (Laryngoscope, 2015)
OBJECTIVES/HYPOTHESIS: Compare outcomes of hypopharyngeal carcinoma that received conventional radiotherapy versus intensity-modulated radiotherapy (IMRT). STUDY DESIGN: Retrospective single-institution trial. METHODS: Between April 1990 and May 2011, 100 patients with hypopharyngeal cancer underwent curative radiotherapy (RT) at our institution: 50 with IMRT and 50 with conventional RT. The median age was 63 years. There were 12 T1, 22 T2, 37 T3, and 28 T4 patients. The majority of patients (82%) had nodal disease: 54% N2 and 8% N3. The majority of patients (83%) received chemotherapy. Of the patients who received chemotherapy, 84% received a platinum-based regimen. The median RT dose was 7,000 cGy. The majority of patients (62%) had prophylactic percutaneous endoscopic gastrostomy tube placement. Toxicities were reviewed. Local control (LC), locoregional control (LRC), freedom from distant metastasis (FFM) rates, functional larynx preservation (LP), laryngectomy-free survival (LFS), and overall-survival (OS) curves were generated using the Kaplan-Meier method. The log-rank test was used to test prognostic variables. RESULTS: With a median follow up of 48.4 months, the 3/5-year LC, LRC, FFM, LP, LFS and OS rates were 74%/69%, 77%/74%, 70%/66%, 51%/29%, 49.6%/31.8%, and 49%/34%, respectively. The median OS was 2.9 years. The 3-year LC rate for IMRT was 77% versus 81% for conventional RT (P = .91); 3-year LRC for IMRT was 85% versus 76% for conventional RT (P = .32). There was no increased local failure with IMRT. There was no difference in the rate of stricture with IMRT (32%) versus conventional RT (25.3%) (P = .86). CONCLUSIONS: IMRT achieved comparable LC and LRC rates to conventional RT.